2022
DOI: 10.1002/he.20444
|View full text |Cite
|
Sign up to set email alerts
|

The cost of academic dismissal and attrition from students on academic probation

Abstract: Policies on academic probation and dismissal have existed in the American higher education system for decades to maintain academic quality and encourage students to improve their performance. Research has aimed to clarify the relationship between academic probation, dismissal, and retention, yet differing results emerge. Furthermore, the literature is sparse on the financial implications incurred as a result of academic dismissal or student attrition once on academic probation. The aim of this study explores f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Institutions that admit students who do not stay in the program lose the tuition and fees that were expected from those students. This attrition is significant among students who are struggling academically such as course repeaters 8…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Institutions that admit students who do not stay in the program lose the tuition and fees that were expected from those students. This attrition is significant among students who are struggling academically such as course repeaters 8…”
Section: Introductionmentioning
confidence: 99%
“…This attrition is significant among students who are struggling academically such as course repeaters. 8 The financial implications of nursing student course repetition have been minimally studied. A scoping review of the literature 3 found only 1 article that addressed the topic.…”
Section: Introductionmentioning
confidence: 99%